Apoptosis Pathway–Associated Proteins Are Frequently Expressed in Melanoma: A Study of 32 Cases With Focus on Acral Lentiginous Melanoma - Ledesma, DA (2024)
Acral lentiginous melanoma (ALM) is an aggressive type of cutaneous melanoma (CM) that arises on palms, soles, and nail units. ALM is rare in White population, but it is relatively more frequent in dark-skinned populations. There is an unmet need to develop new personalized and more effective treatments strategies for ALM. Increased expression of antiapoptotic proteins (ie, BCL2, MCL1) has been shown to contribute to tumorigenesis and therapeutic resistance in multiple tumor types and has been observed in a subset of ALM and mucosal melanoma cell lines in vivo and in vitro. However, little is known about their expression and clinical significance in patients with ALM. Thus, we assessed protein expression of BCL2, MCL1, BIM, and BRAF V600E by immunohistochemistry in 32 melanoma samples from White and Hispanic populations, including ALM and non-ALM (NALM). BCL2, MCL1, and BIM were expressed in both ALM and NALM tumors, and no significant differences in expression of any of these proteins were detected between the groups, in our relatively small cohort. There were no significant associations between protein expression and BRAF V600E status, overall survival, or ethnicity. In summary, ALM and NALM demonstrate frequent expressions of apoptosis-related proteins BCL2, MCL1, and BIM. Our findings suggest that patients with melanoma, including ALM, may be potential candidates for apoptosis-directed therapies.